Development of Animated Video Learning Media to Improve the Way of Ablution for Junior High School Students - Husain, Husain; Amin, Muh. Agil; Astuti, Sindi (Educational Journal of Learning Technology, 2025)
This study aims to analyze the need, validity, and effectiveness of animated videos in improving ablution skills of seventh-grade students of SMPN 1 Rongkong. The research method used is Research and Development (R&D) with the ADDIE development model. The subjects of the study were seventh-grade students of the 2024/2025 academic year. Data were collected through interviews, observations, and questionnaires, and then analyzed both descriptively and quantitatively. The results showed that the developed animated videos received validation from media experts at 72% (valid), material experts at 96% (very valid), and language experts at 88% (very valid). The effectiveness test through ablution practice showed a success rate of 91.43% (effective). Thus, animated videos are deemed feasible and effective for use as learning media to improve students' ablution skills.